Promoting Pancasila Student Profile in Teaching and Learning English in Senior High School - Rizarni, Aulia Noor; Priyana, Joko (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine the strategies used by teachers to promote and discover factors that influence the promotional activities of the Pancasila Student Profile in English learning process. This research used a case study method and was carried out in three Yogyakarta SHS. Data were collected by interviewing English teachers, analyzing teaching modules, and observing learning process. The data obtained were then analyzed using interactive model by Miles, et.al (2014). The results are: (1) Activities to promote Pancasila student profiles integrated into the content of the text, employing storytelling, habituation and field trips (2) Factors that influence the promotion of Pancasila student profiles are support from schools, facilities, teacher mastery and trust, strategies, students' awareness and learning process